HUBUNGAN PRASANGKA MAHASISWA YANG BERMUKIM DI KOTA MAKASSAR DENGAN INTERAKSI SOSIAL TERHADAP MAHASISWA ETNIS PAPUA DI KOTA MAKASSAR - Musawwir; Gunawan HZ, Arie (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This research entitled Prejudice Relationships with Social Interaction between Students Living in Makassar with Papua Ethnic Students in Makassar. The problem of this research is how to find out prejudice relations with social interaction between a student who resides in Makassar with ethnic Papuan students in Makassar. Research hypothesis, that there is a relationship between prejudice to the social interaction of students who live in the city of Makassar against ethnic Papuan students in Makassar. This study used quantitative research methods. The respondents of survey are conducted by accidental sampling, where researcher determined the respondents based on the characteristics of the study. The respondents numbered 150 people from three different universities in Makassar, where students have an interaction with the ethnic Papuan students in classroom lectures. The technique of data collection uses, namely the large-scale deployment of research to the respondents. The result of this research showed that there is a high prejudice and a high social interaction, based on the two variable coefficient is 0.621 and the significance value of 0.000, which is where p = <0.05. The results showed that students living in Makassar tend to have high prejudice towards ethnic Papuan students in Makassar, but still build an interaction on community. The results also lead to social interaction in the process of dissociative, that contravention.